Optimal Water-Nutrient Norms and Irrigation Regimes of Fine-Fiber St-1651 Cotton Variety in Light Gray Soils of Surkhandarya Region (Texas Journal of Multidisciplinary Studies, 2021)
The article examines the fertilizer thickness irrigation system of fine-grained cotton variety ST-1651 in light gray soils of Surkhandarya region.